PROGRESSIVE LAW ENFORCEMENT TOWARDS HUMAN RIGHTS VIOLATION IN KOTA KUPANG` - Joni Efraim Liunima (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Copyright is creator intellectual wealth so it needs to be protected by the State as a form of responsibility. Responding that problem comes into the world Law Number 28 Year 2014 concerning Copyrights and all violations in UUHC is formulated as delict complaint. Consequence of delict complaint is not all of copyright violations can be asked for the responsibility because law agencies are passive and limited by space and time. Answering that jurisdictional problem then researcher used empirical law research method. The result showed that civil servants investigator (PPNS) Kanwil Kemenkumham NTT and also Kupang Kota Police Resort have done progressive step such as appealing, warning, calling, making statement, stocktaking and confiscation whereas the obstacle factor of progressive law enforcement is knowledge, mindset and in the formula of UUHC there is no section which formulate what the step can be done if criminal matters happen so the suggestions given is law enforcement agencies need an explanation about progressive law enforcement and it is better if in UUHC need to be formulated a step which will be taken if criminal matters happen.keywords : Right, Progressive law, Law Enforcement